Peningkatan Pengetahuan Tanaman Obat Keluarga di SMAN 2 Dumai Melalui Penanaman oleh Mahasiswa KKN Kelompok VIII Universitas Abdurrab - Yessi Rahayu; Joni Joni; Vivi Indriani; Qurrata Miftaurrizka; Ummi Roudhatun Nashihah; Aulia Wulan Sari; Sonia Aufa Sudarmanto; Ayu Cahyati; Reka Octavia; Waode Ernawati; Nurfitriani Nurfitriani; Muhammad Arief Mustaqim; Bintang Ramadhani; Ernita Laowo; Siti Nurfateha; Adek Diah Lestari; Muhammad Ikmal; Muhammad Syifa; Reza Liana; Pina Uli Marbun; Juliati Juliati; Ziyanaroza Ziyanaroza; Putri Ika Mayang Ningrum; Syabrina Rindiani; Annisyah Auliya Dicken; Kartika Syahrina (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service Program (KKN) are one of the mandatory programs that must be carried out by students. This TOGA knowledge increasing activity is a form of the Community Service Program (KKN) work program which aims to increase the knowledge and skills of SMAN 2 Dumai students in cultivating family medicinal plants (TOGA). TOGA can be used to treat various diseases such as fever, fever, cough, stomach ache and itching. Usually the medicinal plants chosen are plants for first aid for minor illnesses such as fever and cough. Through training activities and TOGA planting practices on empty school land, students, especially PMR members, are actively involved in the cultivation process. The results of the activity showed an increase in students' awareness of the benefits of TOGA and their ability to identify and care for various types of medicinal plants. Apart from that, the presence of TOGA in the school environment also contributes to creating a healthier and more beautiful learning environment.